The Elgin–Grey papers 1846–52: a triangular correspondence. Issue 1 (July 2015) - Martin, Ged
Abstract : Extensively published in 1937, the correspondence between Lord Elgin (governor-general of Canada, 1847–54) and Earl Grey (colonial secretary, 1846–52) forms a major scholarly resource for studying the evolution of responsible government. In fact, the correspondence was triangular, with Britain's prime minister, Lord John Russell, an active third party. Most letters from Elgin were routinely submitted to him, and he frequently commented on them. However, Grey controlled the correspondence, filtering Russell's contributions, sometimes summarising his arguments to Elgin without attribution, but ignoring impractical suggestions. Although never formally notified of the triangular character of their correspondence, Elgin probably guessed that he addressed a wider audience. Russell generally supported Elgin, but he was occasionally critical. Appreciation of its triangular character is fundamental for a full understanding of the Elgin–Grey correspondence.